Praktik Komunikasi Pranata Humas dalam Membangun Legitimasi Publik di Era Post-Truth - Ruhainah Ruhainah; Ida Suryani Wijaya (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2026)
This study aims to analyze the communication practices of public relations officers in building public legitimacy in the post-truth era at the Ministry of Religious Affairs of East Kalimantan Province. A qualitative approach was used, employing a case study method through interviews, observations, and document analysis. The results indicate that public relations officers play a strategic role in bridging communication between the institution and the public through the use of digital media and a dialogic approach. Communication strategies are implemented adaptively by tailoring messages and media to audience characteristics. However, communication practices still tend to be informative and reactive, thus failing to fully achieve symmetrical two-way communication. In addressing the challenges of the post-truth era, public relations practitioners engage in rapid clarification, foster transparency, and develop counter-narratives against disinformation. These practices contribute to building public legitimacy, although they are dynamic in nature and require continuous strengthening through more participatory and strategic communication.